2013
DOI: 10.1089/dna.2013.1998
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Roles of Amiloride in Irradiation-Induced Antiproliferative Effects in Glioblastoma Multiforme Cells Involving Akt Phosphorylation and the Alternative Splicing of Apoptotic Genes

Abstract: Apoptosis is a key mechanism for enhanced cellular radiosensitivity in radiation therapy. Studies suggest that Akt signaling may play a role in apoptosis and radioresistance. This study evaluates the possible modulating role of amiloride, an antihypertensive agent with a modulating effect to alternative splicing for regulating apoptosis, in the antiproliferative effects induced by ionizing radiation (IR) in glioblastoma multiforme (GBM) 8401 cells. Analysis of cell viability showed that amiloride treatment sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…We found that their combination had more than additive effects on the suppression of esophageal cancer cell growth in vitro and in nude mouse xenografts. Indeed, previous studies have used combination of amiloride with other agents (such as radiation or morphine) to control glioblastoma or pain (Tang et al, 2013; Ouyang et al, 2012). Thus, future study is needed to further explore the activity of these combined agents in controlling esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We found that their combination had more than additive effects on the suppression of esophageal cancer cell growth in vitro and in nude mouse xenografts. Indeed, previous studies have used combination of amiloride with other agents (such as radiation or morphine) to control glioblastoma or pain (Tang et al, 2013; Ouyang et al, 2012). Thus, future study is needed to further explore the activity of these combined agents in controlling esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, caffeine and digoxin have been used in clinical application. Tang et al suggested that 0.2 mM amiloride modulated cell radiosensitivity and RNA splicing of the apoptotic peptidase activating factor 1 (APAF1) [80]. 1.0 μ m NB-506 mediated splicing inhibition by preventing complete phosphorylation of the SF2/ASF SR protein, affected apoptosis and tumour progression [81].…”
Section: Small Molecules As Drugs For Regulating Rna Splicing In Cancermentioning
confidence: 99%
“…Gene expression profiling data revealed that metformin’s impact on GBM cells mainly involves RNA binding and splicing pathways (Yang 2016); however, this may be an indirect effect through diverse cellular machinery. Another relevant compound is the anti-hypertensive agent amiloride, which can lead to apoptosis and radio-sensitivity through the modulation of APAF1 splicing (Tang et al 2013). Among the analogous of FR901464, Pladienolide B reduced tumor size in glioblastoma U251 xenografts (Mizui et al 2004).…”
Section: Cancer Therapy Via Splicing Modulationmentioning
confidence: 99%